Interleukin-10 Producing T Lymphocytes Attenuate Dermal Scarring. Issue 4 (October 2021) - Short, Walker D.; Wang, Xinyi; Li, Hui; Yu, Ling; Kaul, Aditya; Calderon, Gisele A.; Gilley, Jamie; Bollyky, Paul L.; Balaji, Swathi; Keswani, Sundeep G.
Abstract : Objective: Demonstrate the impact of IL-10 producing T lymphocytes on mediating dermal scarring. Summary Background Data: We demonstrated that CD4 + cells are essential to improving postinjury wound healing and preventing fibrosis. CD4 + subsets secrete differential cytokine and growth factor profiles, though their role in fibrosis is not known. IL-10, a key anti-inflammatory cytokine shown to promote regenerative wound healing, is secreted by some CD4 + subsets. We, therefore, hypothesize that IL-10 producing CD4 + T lymphocyte subsets selectively attenuate dermal wound fibrosis. Methods: IL-10 -/- and wild-type murine splenocytes were enriched for CD4 + lymphocytes and adoptively transferred into severe combined immunodeficient (SCID) mice that received full-thickness wounds which were analyzed at days 7 and 28 for inflammation and collagen content. We then sorted CD4 + CD44 int/low FoxP3 - CD62L + T cells (Tnaive) or CD4 + CD44 Hi FoxP3 - type 1 regulatory (Tr1) T cell subsets from 10BiT murine splenocytes, activated them, and transferred them into wounds. In vitro, dermal fibroblasts were cocultured with Tnaive or Tr1 and the effect on extracellular matrix (ECM) regulation was analyzed. Results: The anti-inflammatory and antifibrotic effects of CD4 + cells on SCID wounds were lost with cells from IL-10 -/- mice. Adoptive transfer of Tr1 into SCID mice resulted in accelerated wound closure at d7 with reduced fibrosis at d28, with Tr1 favoring hyaluronan production by fibroblasts, an ECM molecule implicated in IL-10-induced regenerative healing. Conclusions: IL-10 producing T-lymphocytes, specifically Tr1, regulate inflammatory cell cytokine expression to promote HA-rich ECM deposition and attenuate fibrosis. Promoting IL-10 producing lymphocytes in wounds may be a therapeutic target to promote regenerative wound healing. Abstract : Supplemental Digital Content is available in the text